Employment of Audacity Application for Vocabulary Lessons - Fude, Yan; Andrew, Beatrix; Amrina, Amrina (Journal International of Lingua and Technology, 2022)
In this day and age, technology has explored every line, including the world of education. There are many technologies that can be used in education, one of which is Audacity. Audacity is an application that is used to edit sound or audio. This application can be downloaded via desktop or android. One of the Arabic language learning used in this application is Istima’. This research is a qualitative descriptive research. Descriptive research is research that can examine literature reviews or describe phenomena that occur in the world of education. The purpose of this study is to describe the use of the Audacity application as an effort to strengthen students' interest in learning, this study uses qualitative research methods that are literature studies, while the sources of literature in this study are journals and books in the form of e-modules. As for how to use the application using an audacity account by utilizing the audacity application.